Implementation of Dialectical Behavior Therapy (DBT) as an Effort to Overcome Emotional Disregulation and Post-Traumatic Disorder Stress (PTSD) in Adolescents Violent Behavior and Suicide Attempts - Veno Dwi Krisnanda; Nur Hidayah; M. Ramli. MA (PT FORMOSA CENDEKIA GLOBAL, 2023)
Violent behavior is a situation where a person can endanger himself and others both physically and psychologically. To reduce this violent behavior, it is necessary to carry out a prevention, namely applying Dialectical Behavior Therapy (DBT). Dialectical Behavior Therapy (DBT) is a psychotherapeutic therapy intervention that can help patients control their emotions, accept the current situation, and change the negative behavior that the patient previously carried out towards a more positive behavior. The purpose of this study is to find out how the effect of Dialectical Behavior Therapy (DBT) is on clients with violent behavior of suicide attempts, Emotional dysregulation, Posttraumatic Distress Stress. This research uses the literature study method, namely by searching through electronic databases, Garuda, and Google Scholar. The inclusion criteria used were articles from 2011-2022 and resulted in several significant research articles. The results found using this literature study show that Dialectical Behavior Therapy (DBT) is very effective as an intervention to help patients with violent behavior